2021
DOI: 10.1007/s10072-021-05635-y
|View full text |Cite
|
Sign up to set email alerts
|

Persistent chemosensory dysfunction in a young patient with mild COVID-19 with partial recovery 15 months after the onset

Abstract: Objective It is reported that recovery from COVID-19 chemosensory deficit generally occurs in a few weeks, although olfactory dysfunction may persist longer. Here, we provide a detailed follow-up clinical investigation in a very young female patient (17-year-old) with a long-lasting anosmia after a mild infection, with partial recovery 15 months after the onset. Methods Neuroimaging and neurophysiologic assessments as well as olfactory mucosa swabbing for microbiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The sequence of pathobiological events leading to olfactory dysfunction may include an inflammatory component (Kirschenbaum et al, 2020). Irreparable tissue damage at the level of the OM (Fodoulian et al, 2020;Vaira et al, 2020a) may underlie the persistent anosmia observed in a subset of COVID-19 patients (Cecchini et al, 2021;Renaud et al, 2021).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The sequence of pathobiological events leading to olfactory dysfunction may include an inflammatory component (Kirschenbaum et al, 2020). Irreparable tissue damage at the level of the OM (Fodoulian et al, 2020;Vaira et al, 2020a) may underlie the persistent anosmia observed in a subset of COVID-19 patients (Cecchini et al, 2021;Renaud et al, 2021).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Nine months later, the brain MRI showed no significant structural changes or high signal characteristics in olfactory blubs and cortex. It was reasonable to speculate that the olfactory bulb lesions of the patient had recovered 9 months later (Cecchini et al, 2021(Cecchini et al, , 2022. In previous studies, the RAS system was shown to mediate Ang-(1-7) in the amygdala, hippocampus, and prefrontal cortex, leading to the high expression of ACE2 and thus inducing mood and mental diseases.…”
Section: Brain Imaging Findings After 6 Months Of Rehabilitationmentioning
confidence: 82%
“…Similarly, recent studies in people with post-COVID-19 symptoms found no significant differences in MRI findings between subjects with and without cognitive impairments and fatigue after acute infection (Hellgren et al 2021 ; Huang et al 2022 ). Moreover, despite several studies detecting changes in brain microstructure of people with post-COVID-19 with structural MRI (Colonna et al 2020 ; Freeman et al 2021 ; Hixon et al 2021 ; Nuzzo et al 2021 ; Cecchini et al 2022 ) and DTI (Liu et al 2019 ; Tian et al 2020 ; Qin et al 2021 ), no correlations with fatigue symptoms have been reported. Other recent studies found that post-COVID-19 symptoms were rarely associated with damage of the central or peripheral nervous system (Fleischer et al 2022 ) or alterations in regional cerebral glucose metabolism (Dressing et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%